Anti-inflammatory effects of Morus alba Linne bark on the activation of toll-like receptors and imiquimod-induced ear edema in mice - Lin Umeyama; Besse Hardianti; Shiori Kasahara; Dya Fita Dibwe; Suresh Awale; Satoru Yokoyama; Yoshihiro Hayakawa (BMC, 2021)
Abstract Background Morus alba L. bark has been widely used in traditional medicine for treating several inflammatory diseases, such as hypertension, diabetes mellitus and coughing; however, the molecular mechanisms underlying its anti-inflammatory effects are not well understood. Methods We examined the effects of an extract of Morus alba L. bark (MabE) on Toll-like receptor (TLR) ligand-induced activation of RAW264.7 macrophages using a luciferase reporter assay and immunoassays. For the in vivo experiment, we used an imiquimod-induced ear edema model to examine the anti-inflammatory effects of MabE. Results MabE inhibited the TLR ligand-induced activation of NF-κB in RAW264.7 cells without affecting their viability. Consistent with the inhibition of NF-κB activation, MabE also inhibited the production of IL-6 and IL-1β from TLR ligand-treated RAW264.7 cells. In vivo MabE treatment inhibited the ear swelling of IMQ-treated mice, in addition to the mRNA expression of IL-17A, IL-1β and COX-2. The increases in splenic γδT cells in IMQ-treated mice and the production of IL-17A from splenocytes were significantly inhibited by MabE treatment. Conclusion Our study suggests that the anti-inflammatory effects of MabE on the activation of the macrophage cell line RAW246.7 by TLRs and IMQ-induced ear edema are through the inhibition of NF-κB activation and IL-17A-producing γδT cells, respectively.